A laboratory study of global-scale wave interactions in baroclinic flow with topography I: multiple flow regimes - Read, P; Risch, S (2011)
A laboratory investigation is presented with the aim of studying systematically the diversity of flows resulting from the interaction of a baroclinic flow with periodic bottom topography. Flow visualisation and particle-tracking experiments were performed using a differentially heated rotating annulus of fluid with sinusoidal bottom topography. Multi-directional regime scans with varying initial locations in parameter space revealed a rich variety of flow regimes, including those with near-axisymmetric flow at upper levels and a weak stationary wave forced by the topography which is evanescent at upper levels, and flows with a strong forced wave at all heights both with and without travelling baroclinic waves. A range of time-dependent and vacillating flows was also found. The parametric occurrence of the principal regimes agrees well with a number of earlier studies, which covered a more limited range and at lower resolution in parameter space. It is clear from these results that multiple flow states at the same point in parameter space are very common in baroclinically unstable flows with topography. The parametric extent of the influence of the topographically forced stationary waves was shown to be qualitatively consistent with the well-known Charney-Drazin criterion for vertical wave propagation. © 2011 Taylor and Francis.